Pengembangan Media Pembelajaran Explosion Box pada Pembelajaran IPA Sistem Pernapasan Manusia di Kelas V SD Negeri 101928 Rantau Panjang Tahun Ajaran 2023/2024 - Muliani, Muliani; Herdyana, Thessa; Ramadhan, Nuri (Medan Resource Center, 2024)
This research aims to develop Explosion Box media for teaching the human respiratory system and to assess its feasibility and practicality based on evaluations by educators and students. The study adopts the Borg and Gall development model and follows six stages: potential problems, data collection, product design, product validation, product revision, and product testing. Data collection involved questionnaires from material and media experts to determine feasibility and responses from teachers and students to evaluate practicality. The subjects were fifth-grade students at SD Negeri 101928 Rantau Panjang, Pantai Labu District. The results showed that the Explosion Box media received a feasibility score of 77% from media experts and 80% from material experts. Teachers’ responses indicated a practicality score of 1, demonstrating the effectiveness of the media. The developed Explosion Box media is suitable and practical for teaching the human respiratory system in science lessons for fifth-grade students. This media offers an innovative and engaging approach to enhance student understanding of complex scientific concepts.